The value of public service broadcasting in Japan: The life satisfaction approach - Naoko Okuyama (International Telecommunications Society (ITS), 2017)
Evaluation of amenities and benefits of public service broadcasting is crucially important with the accelerated convergence of broadcasting and telecommunications and the increasing heterogeneities of media use by individuals. With the use of the microdata provided from a survey carried out by Japanese public service broadcaster, we attempted to elucidate the effect of viewing public service broadcasting on individual well-being using the life satisfaction approach in quantitative, monetized terms. Crucial findings of our analysis include that viewing frequency of public service broadcasting is negatively associated with life satisfaction, even after successfully addressing the endogenous nature of television viewing. It is also found that the detrimental effect of viewing public service broadcasting has a considerable monetary impact. In the sense of studying the demand side, our exploration of the value of conventional viewing of public service broadcasts will provide a valuable comparative benchmark future research in this domain.
Keywords: D61; H41; I31; L82; 330; Life satisfaction approach; Non-market valuation; Television viewing; Public service broadcasting